Anti-inflammatory Nanomedicine for Cardiovascular Disease - Katsuki, Shunsuke; Matoba, Tetsuya; Koga, Jun-ichiro; Nakano, Kaku; Egashira, Kensuke (Frontiers in Cardiovascular Medicine, 2017)
Coronary artery disease, in the development of which inflammation mediated by innate immune cells plays a critical role, is one of the leading causes of death worldwide. The 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) are a widely used lipid-lowering drug that has lipid-independent vasculoprotective effects such as improvement of endothelial dysfunction, anti-oxidant properties and inhibitory effects on inflammation. Despite recent advances in lipid lowering therapy, clinical trials of statins suggest that anti-inflammatory therapy beyond lipid lowering therapy is indispensible to further reduce cardiovascular events. One possible therapeutic option to the residual risk is to directly intervene in the inflammatory process utilizing a nanotechnology-based drug delivery system (Nano-DDS). Various nano-sized materials are currently developed as DDS including micelles, liposomes, polymeric nanoparticles, dendrimers, carbon nanotubes, and metallic nanoparticles. The application of Nano-DDS to coronary artery disease is a feasible strategy since the inflammatory milieu enhances incorporation of nano-sized materials into mononuclear phagocytic system and permeability of target lesions, which confers Nano-DDS on ‘passive-targeting’ property. Recently, we have developed a polymeric nanoparticle-incorporating statin to maximize its anti-inflammatory property. This statin nanoparticle has been tested in various disease models including plaque destabilization and rupture, myocardial ischemia-reperfusion injury, and ventricular remodeling after acute myocardial infarction, and its clinical application is in progress. In this review, we present current development of DDS and future perspective on the application of anti-inflammatory nanomedicine to treat life-threatening cardiovascular diseases.